Plasma microRNA expression and immunoregulatory cytokines in an Indian population occupationally exposed to cadmium. Issue 1 (12th September 2022) - Mitra, Prasenjit; Goyal, Taru; Sharma, Praveen; Sai Kiran, Gangam; Rana, Shweta; Sharma, Shailja
Abstract: Following its accumulation in the body, cadmium (Cd) exposure is associated with devastating effects on multiple organ system of the human body. The immune system is one of the sensitive targets for Cd‐induced toxicity. Recently, studies have demonstrated a significant role of Cd in inducing epigenetic alterations. With this background, the present study was planned to study the changes in candidate microRNA (miRNA) expression associated with immune regulation in occupationally Cd‐exposed workers. One hundred individuals involved in welding and metal handicraft manufacturing, while 80 apparently healthy subjects without any prior history of occupational exposure were recruited for the study. Blood Cd level was determined by atomic absorption spectrometry. Serum cytokine levels were measured using an enzyme‐linked immunosorbent assay and serum miRNA expression of candidate miRNAs (miR‐146a, miR‐210, and miR‐222) were determined by real‐time polymerase chain reaction. The median Cd level (2.40 μg/L) in the occupationally exposed workers was significantly higher than the nonexposed subjects (0.90 μg/L). Among the cytokines, interleukin‐4 (IL‐4), and tumor necrosis factor‐alpha (TNF‐α) were significantly higher while IL‐2 and IL‐10 were significantly lower in the exposed. The expression level of miR‐146a and miR‐222 were significantly different between the groups with the former showing downregulation and later showing upregulation. Correlation analysis revealed a positive and negative association of miR‐222 and miR‐146a with blood cadmium level, IL‐17 as well as TNF‐α, respectively. Furthermore, the in‐silico analysis revealed a significant role of the studied miRNAs in various cellular and genetic pathways. The findings of the present study demonstrate significant involvement of Cd‐induced alteration in miRNAs in varied immune regulatory changes in exposed individuals.